Yea me ether did you ever find the answer
Answer:
Links are blurry please type (:
Step-by-step explanation:
Answer:
![(\frac{dy}{dt})^2=sin^2t](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3Dsin%5E2t)
Step-by-step explanation:
![y=cost](https://tex.z-dn.net/?f=y%3Dcost)
DE :![(\frac{dy}{dt})^2=1-y^2](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3D1-y%5E2)
If y is a solution of given DE then it satisfied the DE.
Differentiate w.r.t t
![\frac{dy}{dt}=-sint](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdt%7D%3D-sint)
Using the formula
![\frac{d(cosx)}{dx}=-sinx](https://tex.z-dn.net/?f=%5Cfrac%7Bd%28cosx%29%7D%7Bdx%7D%3D-sinx)
LHS:![(\frac{dy}{dt})^2=(-sint)^2=sin^2t](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3D%28-sint%29%5E2%3Dsin%5E2t)
RHS
![1-y^2=1-cos^2t=sin^2t](https://tex.z-dn.net/?f=1-y%5E2%3D1-cos%5E2t%3Dsin%5E2t)
By using the formula
![sin^2t=1-cos^2t](https://tex.z-dn.net/?f=sin%5E2t%3D1-cos%5E2t)
LHS=RHs
Hence, y is a solution of given DE
![(\frac{dy}{dt})^2=sin^2t](https://tex.z-dn.net/?f=%28%5Cfrac%7Bdy%7D%7Bdt%7D%29%5E2%3Dsin%5E2t)
Expanded form is writing out everything and no simplifying.
A. c times c
B. t times t times t times t
C. 2 times x times x times x
D. 4 times 4 times h times h
E. 2 times 2 times 2 times l times l times l
F. a times a times a + 7 times b times b
Hope this helps :)